Deferoxamine inhibition of malaria is independent of host iron status. - Hershko, C; Peto, T (1988)
The mechanism whereby deferoxamine (DF) inhibits the growth of malaria parasites was studied in rats infected with Plasmodium berghei. Peak parasitemia was 32.6% (day 14) in untreated controls and 0.15% (day 7) in rats receiving 0.33 mg/g in 8 hourly DF injections, subcutaneously. DF inhibition of parasite growth was achieved without any reduction in transferrin saturation or hemoglobin synthesis and with only a partial (56%) depletion of hepatic iron stores. Dietary iron depletion resulted in anemia (hematocrit 25 vs. 46%), microcytosis (MCV 54 vs. 60 fl), and reduced transferrin saturation (17 vs. 96%) without any effect on infection (peak parasitemia 30 vs. 36%). Similarly, parenteral iron loading with ferric citrate over 10 d (75 mg iron/kg) failed to aggravate infection. In a search for evidence of direct interaction between DF and parasitized erythrocytes, gel filtration and ultrafiltration was performed on hemolysates obtained from in vivo 59Fe-labeled parasitized erythrocytes. This showed that 1.1-1.9% of the intracellular radioiron was located in a chelatable, labile iron pool. Incubation of intact cells with 0-500 microM DF resulted in a proportional increase in intracellular iron chelation, and the chelation of all available labile intracellular iron was completed within 6 h. These observations indicate that the severity of P. berghei infection in rats and its in vivo suppression by DF are independent of host iron status and suggest that DF inhibition of malaria involves intracellular chelation of a labile iron pool in parasitized erythrocytes.